Avaliação energética de dois sistemas de produção de milho - Bernardi, Lorena de Moraes (2008)
Consumption of energy in a system of production is one of the most worrying things in agricultural activity. Accordingly, the calculation of the energy balance is one of the most important tools when you want to assess the sustainability of agroecosystems. This study aimed to evaluate the consumption and production of energy in two systems of production of corn, one of ecological base and other conventional, developed in two agricultural properties, both located in Pelotas/RS. Questionnaires modified in Marchioro (1985), were applied to farmers, with the aim of characterizing the production units, the composition of families, the hours devoted to each operation and management practices and types and quantity of inputs used. By the existing scientific literature, the equivalent energy were identified that are present in the stages of production processes, which led to measure the consumption (input), energy (human / animal activity, agricultural chemicals, fuel ...) and the energy produced (output) for biomass derived from their systems, which was obtained through the collection of a sample of the population of corn plants chosen at random, which after passing through processes of drying and weighing in laboratory provided data representative of the total production of biomass in cultivated areas, data which were finally converted into equivalent energy production. The entrances and exits of energy in both systems were related and led their respective energy balances. The total consumption of energy in 1 (one) hectare of the ecological base system of production (1,38 MJ) is lower than in 1 (one) hectare of conventional system (5.789,10 MJ) and energy production in the same area proved to be greater in the production system of ecological base (321.225,30 MJ) than in conventional (166.055,02 MJ). It was confirmed that the energy balance in the ecological base system of production (232,93) is most effective when compared to the conventional system (29,20).